2021
DOI: 10.21468/scipostphyscore.4.2.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantum hypothesis testing in many-body systems

Abstract: One of the key tasks in physics is to perform measurements in order to determine the state of a system. Often, measurements are aimed at determining the values of physical parameters, but one can also ask simpler questions, such as ``is the system in state A or state B?''. In quantum mechanics, the latter type of measurements can be studied and optimized using the framework of quantum hypothesis testing. In many cases one can explicitly find the optimal measurement in the limit where one has simultaneous acces… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 236 publications
0
6
0
Order By: Relevance
“…On a somewhat different note, an information-theoretic quantity, known as the capacity of entanglement [20][21][22][23] or capacity in short, recently gained some attention, for example, in the context of the information paradox [24,25]. It was shown that, like entanglement entropy, capacity could also truly probe the phase transition that happens at the Page time [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a somewhat different note, an information-theoretic quantity, known as the capacity of entanglement [20][21][22][23] or capacity in short, recently gained some attention, for example, in the context of the information paradox [24,25]. It was shown that, like entanglement entropy, capacity could also truly probe the phase transition that happens at the Page time [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…More generally, one can define capacity in terms of the relative entropy variance between two density matrices. When one of the density matrix becomes maximally mixed, i.e., proportional to the identity, the relative entropy variance becomes the capacity[23].…”
mentioning
confidence: 99%
“…the examples and discussions in Refs. [38,[61][62][63][64][65]. Also the Schatten distances have been studied in field theories [37,38,[65][66][67][68][69], but not as much as the relative entropy, most likely because of the more difficult replica approach (see below) necessary for their determination.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we address this question and find an affirmative answer. We consider a different entanglement measure, the capacity of entanglement (CoE) [36][37][38], first considered in the Kitaev model to describe topologically ordered states [39] and to understand the thermodynamic properties of the entanglement spectrum [40]. Very recently, it has received considerable attention, for example, in local operator excitations [41], random pure states [42], and in the context of holography and black hole information problem, where it is shown to capture partially entangled states in replica wormhole geometry [43,44].…”
Section: Introductionmentioning
confidence: 99%